Capital Structure Comparison in Low Cost Airlines Industry in UK. - GHARGE, VIVEK (2014)
This report presents with the research, analysis and comparison of the capital structure for the UK low cost airline industry with the main focus on Monarch airlines limited our client. This report tests the presumption of maintaining a reasonable level of leverage in an airlines industry to get a good financial results and also seeks to establish this level by maintaining the average weighted cost of capital of around 9-10 %. (Bloomberg) The research identifies the biggest airline companies which use capital efficiently to generate return on investment higher than cost of capital so that company is in profit. In these companies the equity element almost corresponds to around 75 % plus 20 % for long term debt and less than 5 % for short term debts. (Bloomberg) However it is not necessary that having certain percentage of capital structure and having established the average cost of capital will result into profitability. A case study of Southwest airlines is identified for supporting the claim of maintaining the certain level of leverage and equity so as to achieve constant weighted average cost of capital. In addition, this report presents recommendation to the client on the various ways of sources of financing that would help the client to get rid of short term debt and get back to their day to day businesses.